2013
DOI: 10.1248/bpb.b13-00018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition by Hydrogen Sulfide of Rabbit Platelet Aggregation and Calcium Mobilization

Abstract: Hydrogen sulfide (H 2 S), a gasotransmitter, plays a variety of roles in the mammalian body including the cardiovascular system. Given evidence that H 2 S donors including NaHS inhibit human platelet aggregation, we examined and characterized the effects of NaHS on rabbit platelet aggregation and cytosolic Ca 2+ mobilization. Rabbit platelet aggregation was determined in platelet-rich plasma (PRP) and washed platelets. Intracellular Ca 2+ levels were monitored in Fura2-loaded washed platelets. NaHS prevented r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
6

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 20 publications
0
10
0
6
Order By: Relevance
“…In the advanced atherosclerosis model of Apo E KO mice, subendothelial infiltration of monocytes/macrophages and platelets was observed, suggesting intimate interactions of platelets and macrophages in early atherosclerosis [85]. A recent paper by Nishikawa et al demonstrated the role of hydrogen sulfide (H 2 S), a gasotransmitter, in inhibiting platelet aggregation by interfering the cytosolic Ca 2+ mobilization in a cAMP-dependent manner, comparable to what is observed for nitric oxide (NO) [86]. Studies by us have suggested that functions regulated by NO require the presence and activation of TSPO [87].…”
Section: Results With Discussionmentioning
confidence: 91%
“…In the advanced atherosclerosis model of Apo E KO mice, subendothelial infiltration of monocytes/macrophages and platelets was observed, suggesting intimate interactions of platelets and macrophages in early atherosclerosis [85]. A recent paper by Nishikawa et al demonstrated the role of hydrogen sulfide (H 2 S), a gasotransmitter, in inhibiting platelet aggregation by interfering the cytosolic Ca 2+ mobilization in a cAMP-dependent manner, comparable to what is observed for nitric oxide (NO) [86]. Studies by us have suggested that functions regulated by NO require the presence and activation of TSPO [87].…”
Section: Results With Discussionmentioning
confidence: 91%
“…6 C. Analysis of the data does not show any statistical differences between SUL and NOSH-SUL. It should be noted that NOSH-SUL releases NO and H 2 S [29] both of which can have independent anti-platelet properties [41–43] .…”
Section: Resultsmentioning
confidence: 99%
“…More studies may provide deeper insights into how TSPO is involved in molecular biological mechanisms and biological functions of erythrocytes. [86]. Studies by us have suggested that functions regulated by NO require the presence and activation of TSPO [87].…”
Section: Results With Discussionmentioning
confidence: 99%